The Influence of Ratings and Electronic Word of Mouth (EWOM) on Online Shop Customer Trust (Shopee) - Moh. Aep Nurjamad; Abdi Kurniawan Gulo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted on student of the Faculty of Economics, Department of Management, PASIM national university who use an online shop (shopee). The purpose of this study was to determine how much contribution the influence of ratings and electronic word of mouth (ewom) has on customer trust both partially and simultaneously at shopee. The research methods used in this research are descriptive methods and associative methods.in this study, the unit of analysis is the Faculty of Economics, Department of Management, Regular Morning Class, Pasim National University. The sample in this study were 110 respondents. Proportional sampling is the sampling technique used in this study. The analysis method uses multiple linear regression analysis, in addition, validity and reliability testing and research instruments are also carried out. Based on the results of calculations using SPSS Version 25, it shows the influence of rating variables on costumer trust by 2.4% and electronic word of mouth variables on customer trust by 42.9%.Simultaneously, the rating and electronic word of mouth variables contribute or influence customer trust by 0.453 or 45.3%. This value shows that good rating and electronic word of mouth (ewom) variables will increase customer trust